Mediatization: A grand concept or contemporary approach? - Kho, Suet Nie; Chang, Peng Kee; Ahmad, Abdul Latiff (Elsevier Ltd., 2014)
Mediatization is a concept to encompass the changes brought by media into every aspect of our lives. It goes beyond the conventional textual analysis, production economic-politics and audiences’ studies. This paper therefore dissects the concept of mediatization and traces the researches done on it. Mediatization was also compared to mediation in terms of versatility in describing the totality of media impact.Mediatization researches need to be conducted in Asia's vibrant media landscape in its developed and developing countries.The researchers concluded that mediatization needs to be refined by further researches to be a contemporary media studies approach.